Performing image confusion and diffusion using two dimensional triangle functional chaotic maps - Prasetyo, Heri; Rosiyadi, Didi; Horng, Shi Jinn; Setiawan, Iwan; Basuki, Akbari Indra (International Journal of Advances in Intelligent Informatics, 2021)
Currently, with a malicious attacker against the authorization of an image it is necessary to have a method to secure the content of the image. Therefore this paper presents a new technique for performing image confusion and diffusion using Two Dimensional Triangle Fractional Combination Discrete Chaotic Map (2D-TFCDM). The image confusion requires a set of 2D-TFCDM chaotic random numbers to relocate the pixel locations of plain or secret images. At the same time, image diffusion utilizes the chaotic numbers to modify the pixel values of confused image. The proposed method performs well in terms of visual investigation and objective quality assessment on the confused and diffused images. In addition, it offers a promising result for the grayscale and color image with simple computation, which the experiment results demonstrate that the proposed method outperforms other existing methods under several types of visual observation, correlation coefficients, entropy, UACI, NPCR.